Performance Optimization and Field Validation of Post-Grouting Geopolymer Materials for Pile Foundations: Microstructural Insights and Environmental Durability - Chongchong He; Zhen Xu; Jing Wang; Pan Li; Yangyang Xia; Chao Zhang; Zhenpeng Chen; Wei He (Buildings)
To investigate the potential application of geopolymer materials in pile foundation post-grouting engineering, this study utilized industrial solid wastes such as fly ash (FA), slag (SL), and steel slag (SS) to prepare geopolymer grouting materials (GGMs) with various mix proportions. The fluidity, setting time, bleeding rate, and mechanical properties of these materials were evaluated to determine the optimal mix proportions for pile foundation grouting. Furthermore, the influence mechanisms of different maintenance conditions on material performance were investigated, including unconfined compressive strength, flexural strength, and microstructural changes. The results indicated that when the SL-to-FA ratio was 1:1, the GGMs satisfied the requirements for pile foundation grouting, and their mechanical properties significantly improved with extended curing time. Under Yellow River water maintenance conditions, the materials formed a dense three-dimensional network of hydrated products, notably enhancing their mechanical characteristics. Additionally, field tests confirmed that GGMs effectively improved the shear strength of the pile–soil interface. The grout distribution pattern on the pile side exhibited a “compaction-splitting” mechanism. These research findings provide theoretical support for applying geopolymer materials in pile foundation grouting engineering.